(3GdJfGSH Hjf SdWI QFjS GdOhdI heSFhdjJg aj GdOSGJjQ GdYQHjI (B/s - (3GdTcQj, Ydj jhSa,s 1969- ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2012)
(3JHGjf ehba GdOSGJjQ GdYQHjI ef JfXje eSDhdjI QFjS GdOhdI, Hjf ef fCi HGdQFjS Yf GdeSDhdjI YedG HeHOC (B((3GdQFjS eUhf hZjQ eSDhd(B)(3, cGdOSJhQ GdEeGQGJj hGdJhfSj hGdCQOfj hGdHMQjfj hGdbWQj, hHjf ef fU Ydi eSDhdjI GdQFjS Ydi fMh HOG ajg GdQFjS hGbYG eUhf hZjQ eSDhd, aGdOSJhQ GdShQi eKdG jTJQW deSGAdI GdQFjS JhLjg GdGJgGe Edjg ef bHd cd CYVGA eLdS GdTYH ai GdCbd (B((3e (B91) (3hgh CeQ CbQH ddGSJMGdI efg ddJMbb adG jecf JUhQ ELeGY cd CYVGA GdSdWI GdJTQjYjI Ydi eSCdI hGMOI hdGSjeG ai Xd fXGe GdMRH GdhGMO, GdPi jgjef JdbGFjG Ydi cd eDSSGJ GdOhdI heaGUdgG(B. (3heKdeG JJHGjf ehba GdOSGJjQ GdYQHjI aj eSGAdI GdQFjS, JJHGjf ehbagG aj GdfU Yf eSDhdjI GdQFjS Yf GdLQGFe GdJj jecf eSGAdJg YdjgG, agfGc ef Vjb fWGb eSDhdjJg ai eSGFdJg Yf LQjeI GdNjGfI GdYXej abW cGdOSJhQ GdShQj hGdLjHhJj hGdehQjJGfj hLRQ GdbeQ hHjf ef hSY ef fWGb eSDhdjg GdQFjS bjGSG ddUdGMjGJ GdeMOOI GdJi fCWgG Hg GdOSJhQ, cGdOSJhQ GdYQGbi dSfI (B205(3, GdPi SGAd GdQFjS Yf LQjeg GdNjGfg GdYXei hGdMfK HGdjejf hGfJgGc GdOSJhQ hYOe GdcaGAI hGdfRGgI (B. (3ai GdhbJ GdPi jJeJY ajg GdQFjS ai Xd GdOSJhQ GdePchQ EdG HUdGMjGJ OSJhQjI eMOOI(B. (3hYdi VhA gPG jfGbT gPG GdcJGH eSCdI JfGSH UdGMjGJ GdQFjS GdOSJhQjI eY SdWGJg GdeefhMI ai Xd GdOSGJjQ GdYQHjI GdbGFeI(B. s
(3HHdjhLQGajI (B: (3UaMI (B239-246.s
Keywords: (3QDSGA GdLeghQjIs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3GdHdGO GdYQHjIs; (3GdbGfhf GdOSJhQjs -- (3GdHdGO GdYQHjIs